Seasonal Differences in Organo Chlorine Pesticide Residues in Southern Iraqi Marsh Fish: Perbedaan Musiman dalam Residu Pestisida Organo Klorin pada Ikan Rawa Irak Selatan - Jabeir, Afaq M.; Abduljaleel, Salwa A.; AL-Saad, Hamid T. (Universitas Muhammadiyah Sidoarjo, 2024)
The contamination of two fish species (Oreochromis niloticu and Liza abu) by organochlorine pesticides in southern Iraqi wetlands between the winter of 2021 and the fall of 2022 during several seasons is the subject of this study, To ascertain these OCP, mussel samples of these fish have been collected and extracted. Analysis of organochlorine pesticides was done by using gas chromatography-mass spectrometry (GC-MS). It was discovered that each of these species contained varied concentrations of 14 different kinds of chlorine pesticides. Seasonal variation of these OCPs has been studied, as have the levels of alpha-, delta-, lindane, lindane, hexachlor, aldrin, epoxyheptachlor, D.D.E, dieldrin, D.D.D , endrin aldehyde, endrin ketone, methyl chloride, endrin, and endosulfan. Oreochromis niloticu had mean pesticide concentrations ranging from 0.15 to 1.6 ng/g dry weight in the winter and summer, respectively, while Liza abu had mean pesticide concentrations ranging from 0.13 to 0.7% ng/g dry weight in the winter and summer, respectively. Considering the data at hand, this study—